Persepsi Masyarakat Muslim Desa Aek Raso AFD B Tentang Layanan Agen BRILink - Azzikri, Muhammad Dafiq; Syahputra, Dasa Syawal; Suhendri, Suhendri (Darul Yasin Al Sys, 2025)
This study aims to analyze the perceptions of the Muslim community in Aek Raso Village towards the services provided by the BRILink Agent, managed by Mr. Dimas Purwanto since 2017. The research uses a descriptive quantitative approach with a survey method, involving 40 respondents from a total of 160 Muslim residents in Dusun Teratai. The sampling technique applied is Simple Random Sampling, while data collection was conducted through questionnaires, interviews, and observations. The questionnaire used a four-option Likert scale to measure the community's satisfaction level. The results indicate that the majority of the community is highly satisfied with the services of the BRILink Agent. About 97.5% of respondents stated that BRILink has had a significant impact on the community, 87.5% were satisfied with the speed of transactions, and 93% expressed an overall high level of satisfaction. Factors influencing this satisfaction include ease of access, friendly service, comfortable facilities, cleanliness of the environment, and transaction efficiency. The study concludes that the BRILink Agent services in Aek Raso Village successfully meet the community's needs for easy, fast, and efficient access to banking services. These findings highlight the importance of service quality in shaping positive community perceptions and enhancing financial inclusion in rural areas.